To Determine Frequency of Radial Inclination in Normal Wrists of Local Population. (Journal of Pakistan Orthopaedic Association, 2023)
Objective: To determine the radial inclination in normal wrists of our local populationMaterials and Methods: This is a descriptive cross-sectional study that was conducted upon 100 volunteers in the orthopedic surgery unit at Mardan Medical Complex Mardan from January 2021 to June 2021. Data about age and gender was collected. Antero-posterior X-rays of normal wrists were taken. Percentages, frequencies and mean ± SD were calculated with SPSS (version 10) for the age, sex and radial inclination.Results: The mean age of overall 100 normal subjects was 38.89 ± 12.98 years. The mean age of males was 37.10 ± 12.90 years and it was 40.26 ± 13.18 years for females. There were 59 male subjects and 41 female subjects with a male to female ratio of 1.44 to 1 in this study group. The male subjects as compared to females had higher radial inclination. The old age subjects also had higher values. Our population had different radial inclination from that of the Mexican race. The mean was 24.50 degrees ± SD 1.98 for radial inclination of our normal population. The minimum was 20.50 degrees and the maximum 28.50 degrees having range of 8 degrees.Conclusion: The average value is 24.5 ± 1.98 degrees for radial inclination in our normal local adult population and varies with age, gender and race